Osteoporosis Screening: Applied Methods and Technological Trends - de Oliveira, Mario A.; Moraes, Raimes; Castanha, Everton B.; Prevedello, Alexandra S.; Vieira Filho, Jozue [UNESP]; Bussolaro, Frederico A.; García Cava, David (IOP Publishing, 2022)
Bones are continuously remodeled (resorbed and regenerated) to allow fracture healing and skeleton adaptation to stress. When excessive resorption occurs, bone microstructure is deteriorated, leading to osteoporosis. At early stages, osteoporosis usually has no symptoms; most people are diagnosed when a fracture occurs due to disease severity. To prevent fractures, technologies have been developed to identify high risk population eligible to treatment. Fracture risk has been assessed by analyzing the interaction of different energy stimulus with bone tissues as well as by statistical models that evaluate multiple clinical risk factors. The most applied methods are Dual-energy X-ray Absorptiometry and Fracture Risk Assessment tool. As they present some limitations, other technologies have been proposed for such purpose. A survey of the currently applied and emerging methods is here presented in order to provide a scenario of the technological challenges and trends to diagnose osteoporosis.
Keywords: Bones; DXA; electromechanical impedance; fracture risk; osteoporosis diagnosis